Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

There exist the famous theorem about a basis for dual space

Let $\mathbb V$ be finite dimensional vector space over $F$ and $\mathcal{B} = \{\alpha_1, \ldots ,\alpha_n\}$ is basis for vector space $\mathbb V$ then $\mathcal{B^*} = \{f_1, \ldots ,f_n\}$ is basis for dual space $\mathbb V^*$ such that $f_i(\alpha_{j})=\delta_{ij}$

Is the converse of this Theorem true, I explain more:

Let $\mathcal{B^*} = \{f_1, \ldots ,f_n\}$ be basis for dual space $\mathbb V^*$. Does exist $\mathcal{B} = \{\alpha_1, \ldots ,\alpha_n\}$ such that $\mathcal{B}$ would be basis for vector space and $f_i(\alpha_{j})=\delta_{ij}$?

share|improve this question
5  
Since $\Bbb{V}$ is finite-dimensional, there's a natural isomorphism between $\Bbb{V}$ and $\Bbb{V}^{**}$. You can get the converse by applying the original theorem to $\Bbb{V}^*$ and then using that isomorphism. –  Micah Jul 9 '12 at 17:54

1 Answer 1

up vote 4 down vote accepted

Yes, you can prove that via the bidual space $V^{**} = \mathrm{Hom}(V^*,K)$. There is a canonical homomorphism $\iota: V \to V^{**}$ defined by $\iota(v)(f) := f(v)$ for $f \in V^{*}$. It is easy to see that $\iota$ is injective. Since $\dim V^{**} = \dim V^* = \dim V$, it is actually an isomorphism. Therefore, for every $\varphi \in V^{**}$ there exists a $v \in V$ s.t. $\varphi(f) = f(v)$ for $f \in V^*$.

Now, if $\{f_1,\ldots,f_n\}$ is a basis if $V^*$ then the elements $\{\varphi_1,\ldots,\varphi_n\}$ form a basis of $V^{**}$ where $\varphi_i(f_j) := \delta_{ij}$. By the above considerations, each $\varphi_i$ corresponds to an $\alpha_i \in V$ s.t. $f_i(\alpha_j) = \varphi_j(f_i) = \delta_{ij}$. Since $\iota: V\to V^{**}$ is an isomorphism and $\{\varphi_1,\ldots,\varphi_n\}$ is a basis of $V^{**}$ we know that $\{\alpha_1,\ldots,\alpha_n\}$ is a basis of $V$. Its dual basis is then $\{f_1,\ldots,f_n\}$ because $f_i(\alpha_j) = \delta_{ij}$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.